Postavení sourozenců v rodině s dítětem s postižením - Šolaja, Tatiana (Univerzita Karlova, Pedagogická fakulta, 2020)
This thesis discusses the topic of siblings of individuals with disabilities and their position in the family. The theoretical part aims to define family and its functions, specifics of a parent-child relationship, different kinds of nurturing of a child and also discusses the role of an intact sibling in the family with a child with disability. The second part of the theoretical chapter talks about the place of the child with special needs in the family and in the educational environment, presents different attitudes towards inclusive education, defines the disabilities that are relevant for our further research and presents specifics of living with a child with disability from the point of view of the intact sibling. The main aim of the research was to find out how the siblings themselves reflect on the impact of living with a child with disability on their own development and their future. This thesis was based on literature analysis and qualitative research with elements of grounded theory. The main research technique was an analysis of literature and unstructured interviews with five young adult siblings of individuals with disabilities. This method enabled us to gain a complex view of the specifics connected to living with a child with disability. The answers provided us information about the. Práce se zabývá postavením sourozenců v rodině s dítětem s postižením. V teoretické části je nastíněna problematika rodiny, její definice a funkce, přístupu rodičů k dítěti, výchovy a role intaktního sourozence v rodině s dítětem s postižením. Ve druhé polovině teoretické části se práce věnuje dítěte se speciálními vzdělávacími potřebami, uvádí přístupy k inkluzivnímu vzdělávání, charakterizuje specifika jednotlivých postižení, která jsou relevantní pro výzkumnou část a definuje soužití s dítětem s postižením z pohledu intaktního sourozence. Cílem práce bylo zjistit, jak sami sourozenci reflektují vliv soužití se sourozenci s postižením na vlastní vývoj a na svou budoucnost. Výzkum byl založen na základě analýzy ...